2001
DOI: 10.1088/0953-2048/14/7/314
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, magnetization and dc transport properties of MTG-YBa1.8Na0.2Cu3Oycrystal

Abstract: The Na-doping MTG-YBCO crystal with the nominal composition YBa1.8Na0.2Cu3Oy + 40 mol% Y211 has been successfully synthesized by the melted-textured-growth (MTG) method with top seed. The microstructure photographs show that the crystal has a good layered structure with a number of twins. There is a second peak in the magnetization curve for the magnetic field parallel to the c-axis and at 77 K. The field of zero resistance temperature Tc0 shows a power law, H = H0 (Tc0(0)-Tc0(H))n with n = 1.52 for H∥ab and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…5). A universal viewpoint is that the intrinsic planar defects are responsible for U ≈ H −0.5 , while the extrinsic point defects are responsible for U ≈ H −1[14,25]. For our samples the changing of α values from 0.42 to 0.61 imply that the thermally activated dissipative resisThe magnetic field dependence of activation energy for samples with different Gd-diffusion-doping annealing temperatures.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…5). A universal viewpoint is that the intrinsic planar defects are responsible for U ≈ H −0.5 , while the extrinsic point defects are responsible for U ≈ H −1[14,25]. For our samples the changing of α values from 0.42 to 0.61 imply that the thermally activated dissipative resisThe magnetic field dependence of activation energy for samples with different Gd-diffusion-doping annealing temperatures.…”
mentioning
confidence: 79%
“…Various studies along these lines have been carried out on the different basic forms of high-T c oxide superconductors such as YBa 2 Cu 3 O 7−δ , RBa 2 Cu 3 O 7−δ (R = Nd, Eu, Gd, Dy, Ho and Er), Bi 2 Sr 2 Ca 0.8 Cu 2 O 8+δ , etc. [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The details of the method were reported elsewhere [7]. The crystal samples with platelet splitted up from the cleaved plane of the bulk with a single domain.…”
Section: Experiments and Data Analyzementioning
confidence: 99%
“…These studies have shown that Na + favors both theY 3+ as well as the Ba 2+ sites [1][2][3] since the ionic radius of Na + (0.095nm) is comparable to that of Y 3+ (0.093nm) and Ba 2+ (0.135nm). No change in T c has been observed when the doped concentration x < 0.2 in the YBa 2-x Na x Cu 3 O y (YBNCO) [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation